076 Family history of disease is more accurate in women than men: a potential explanation for apparent gender differences in heritability of stroke. Issue 3 (9th February 2012) - Campbell, S; Edwards, H; Sudlow, C
Abstract : Background: Family history studies suggest that heritability of ischaemic stroke is greater in females than males, with an excess of affected female relatives of female stroke patients. We hypothesised that these findings might be explained by gender differences in accuracy of reporting of family history of disease. Methods: (1) Systematic review of published studies comparing accuracy of reporting of family history of disease by gender. (2) Analysis of data from the Generation Scotland Scottish Family Health Study (SFHS), which collected data from 20 000 participants in Scottish families on participants' and their relatives' disease histories, to assess gender differences in offspring-reported parental history of disease, using self-report as the reference standard. Results: Our systematic review identified 33 relevant studies: 31 compared accuracy of family history reports by female vs male informants; 13 compared accuracy of reports on female vs male relatives of informants. Both the systematic review and SFHS analysis found that females reported family history of disease more accurately than males. The systematic review found no clear trend in accuracy of family history reporting by gender of relative being reported on, whereas the SFHS analysis demonstrated greater accuracy of reporting about maternal than paternal history of disease. Conclusion: Gender differences in heritability of ischaemic stroke may be an artefact of inaccurate family history information.